Antihypertensive and Antifibrosis Effects of Acupuncture at PC6 Acupoints in Spontaneously Hypertensive Rats and the Underlying Mechanisms - Xin, Juan-Juan; Dai, Qiu-Fu; Lu, Feng-Yan; Zhao, Yu-Xue; Liu, Qun; Cui, Jing-Jing; Xu, Dong-Sheng; Bai, Wan-Zhu; Jing, Xiang-Hong; Gao, Jun-Hong; Yu, Xiao-Chun (Frontiers in Physiology, 2020)
Long-term hypertension can lead to both structural and functional impairments of myocardium. Reversing the left ventricular myocardial fibrosis has been considered as a key goal for curing chronic hypertension and has long been a hot field of research in recent years. The aim of the present work is to investigate the effect of electroacupuncture (EA) at PC6 on the hypertension induced myocardial fibrosis in spontaneously hypertensive rats (SHRs). Thirty SHRs were randomized into model, SHR + EA, and SHR + Sham EA group, with WKY rats as normal control. EA was applied once a day in 8 consecutive weeks. The cardiac fibrosis as well as the underlying mechanisms were investigated. After 8-weeks EA treatment at PC6, the enhanced myocardial fibrosis in SHRs were characterized by increased of the ratio of left ventricular mass index, collagen volume fraction, elevated content of hydroxyproline (Hyp), as well as the up-regulated expression of collagen I and collagen III in myocardium tissue of SHRs. All these abnormal alterations above in SHR + EA group was significantly lower compared to the model group. In addition, EA at PC6 significantly improved the pathological changes of myocardial morphology. Meanwhile, the increased levels of angiotensin II (Ang II), tumor necrosis factor-α (TNFα) and expression of transforming growth factor β1 (TGF-β1), connective tissue growth factor (CTGF), matrix metalloproteinase (MMP)-2, MMP-9 in serum or heart tissue of SHRs were also markedly diminished by EA. These results suggest that EA at bilateral PC6 could ameliorate the cardiac fibrosis in SHRs, which might be mediated by the regulation of Ang II - TGF-β1 pathway.